Transcriptome profile of 28-4+ intraepithelial lymphocyte natural killer cells of chicken infected by virulent infectious bursal disease virus - Boo, Sook Yee (2019)
Infectious bursal disease (IBV) caused by infectious bursal disease virus (IBDV), has been infecting chicken flocks for more than fifty years exerting a considerable economic impact to the global poultry industry. The virus infection response by chicken natural killer (NK) cells has been inadequately studied due to the limited monoclonal antibodies that are available. Development of 28-4 monoclonal antibody has allowed the identification of chicken intraepithelial lymphocytes (IEL) NK cells. However, the role of IEL-NK cell and its involvement in initiating the innate immune response in fighting the very virulent IBDV (vvIBDV) are still unknown. Therefore, the objective of this study was to identify the transcriptome profile of uninfected CD3- /28.4+ IEL-NK cells and identify the differential expressed genes and small RNAs (sRNAs) in response to vvIBDV infection at 1 and 3 days post infection (dpi). In this study, the chicken was infected by 103 mean egg lethal dosage (ELD50) of vvIBDV strain 0081 for 1 and 3 days. The CD3-/28.4+ IEL-NK cells were isolated from duodenum of the infected chicken. Then, the total RNA was isolated from CD3-/28.4+ IEL-NK cells and used for library preparation, mRNA and sRNA sequencing, and followed by differential expression and pathway analysis. The RNA sequencing (RNASeq) result was validated by NanoString and sRNA sequencing result was validated by RT-qPCR. A total of 12,141 genes were expressed in uninfected chicken IEL-NK cells and most of the genes with high expression are involved in metabolic pathway whereas most of the low expressed genes involved in cytokine-cytokine receptor pathway. There is a total of 1,115 and 1,266 genes differentially expressed (DE) at 1 and 3 dpi respectively. The DE genes at 1 dpi mainly involved in DNA replication, cell cycle, apoptosis whereas the DE genes at 3 dpi involved in inflammation, antiviral response and interferon stimulation. For sRNA sequencing, there are 35 and 16 sRNAs were differentially expressed at 1 and 3 dpi, respectively. The SNORD101, gga-miR-222a and gga-miR-221-3p were up-regulated on Day 1 and 3 whereas gga-miR-30a-50, ggamiR- 142-5p, gga-miR-32-5p and gga-miR-146b-5p were down-regulated on both days. Meanwhile, GAPDH and YWHAZ were the most stably expressed genes in the chicken CD3-/28.4+ IEL-NK cells infected by vvIBDV according to the RT-qPCR result. In conclusion, the immunity of chicken CD3-/28.4+ IEL-NK cells was suppressed at 1 dpi and the proliferation of NK cells was an act of a preparation step for the defense against virus at 2 or 3 dpi. At 3 dpi, the innate immune response was activated as several genes involved in inflammation, antiviral response and recruitment of NK cells to infected area were up-regulated. This is the first study which examined the whole transcriptome profile of chicken NK cells towards IBDV infection, which provides a better insight into the early immune response of chicken NK cells.